P12 Socioeconomic differences and lung cancer survival in germany: differences in cancer therapy and clinical prognostic factors. (3rd September 2019) - Finke, I; Behrens, G; Schwettmann, L; Gerken, M; Pritzkuleit, R; Holleczek, B; Brenner, H; Jansen, L
Abstract : Background: Studies from several countries reported lower lung cancer survival for lower socioeconomic status groups at individual and area level. Assumed reasons are differences in cancer care or tumor characteristics between these different groups. For Germany, this has not yet been investigated in detail. We examined the association between area-based socioeconomic deprivation and lung cancer survival by emphasizing on demographical factors related to the patient, clinical prognostic factors and utilization of cancer therapy. Methods: Patients registered with a primary tumor of the lung (ICD-10 C34) between 2000–2015 in three German population-based clinical cancer registries were eligible for our study. Area-based socioeconomic deprivation on municipality level was measured with the categorized German Index of Multiple Deprivation (GIMD). Our main outcome, survival after cancer diagnosis, was analyzed with Cox regression and we repeated the analysis for subgroups receiving chemotherapy, radiotherapy or surgery. Differences in stage and grading at diagnosis were analyzed with logistic regression. The main models included age, sex, histologic subtype, grading and stage at diagnosis. All analyses were conducted in SAS 9.4. Results: Overall, 22, 905 patients were included of whom 72.9% were male, 23.8% were over 75 years of age, 49.5% were diagnosed with stage IV cancer and 82.7% with non-small-cell lung cancer. Kaplan-Meier five year overall survival estimates from the least to the most deprived quintile were 17.2% [95%-Confidence Interval (CI): 15.8–18.5], 15.9% [14.8–17.2], 16.7% [15.5–17.9], 15.7% [14.5–16.9], and 14.4% [13.3–15.5], respectively. Our main Cox model showed lower survival in the most deprived group compared to the most affluent group (Hazard Ratio (HR) 1.06, 95%-CI 1.01–1.11). This association was more pronounced in the later than in the earlier period of diagnosis [2000–2010: HR 1.03, (0.98–1.09); 2011–2015: HR 1.12, (1.03–1.23)]. No associations were seen for subgroups of patients receiving either chemotherapy, radiotherapy or surgery. When excluding patients diagnosed with stage IV, the effect estimate for the most deprived group was considerably larger [HR 1.15, 95%-CI 1.07–1.24]. Conclusion: Our preliminary results indicate differences in lung cancer survival according to area-based socioeconomic deprivation on municipality level in Germany.